Leaning within a flexible inflation-targeting framework: Review of costs and benefits - Denis Gorea; Oleksiy Kryvtsov; Tamon Takamura (Bank of Canada, 2016)
This note examines the merits of monetary policy adjustments in response to financial stability concerns, taking into account changes in the state of knowledge since the renewal of the inflation-targeting agreement in 2011. A key financial system vulnerability in Canada is elevated household indebtedness: as more and more households are nearing their debt-capacity limits, the likelihood and severity of a large negative correction in housing markets are also increasing. Adjusting the path of policy rates can be effective in reducing the buildup of household debt and the likelihood of a house price correction over the medium term. Such adjustments can also generate a fall in inflation and in output over the short term compared with the case without a policy-rate adjustment. Overall, the estimated benefits of a leaning adjustment tend to be smaller than its social losses, since its impact on the buildup of vulnerabilities is modest and the reduction in the incidence of house price corrections or financial crises is limited.
Keywords: E0; E44; E52; E58; G18; 330; Financial stability; Monetary policy framework